2008
DOI: 10.1124/mol.108.039750
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Vinblastine via c-Jun Autoamplification and p53-Independent Down-Regulation of p21WAF1/CIP1

Abstract: Vinblastine treatment in all cell lines examined causes a robust increase in c-Jun protein expression and phosphorylation and a corresponding increase in activator protein-1 (AP-1) transcriptional activity. We show in KB-3 carcinoma cells that this is due to a strong autoamplification loop involving the proximal AP-1 site in the c-Jun promoter, resulting in highly increased c-Jun mRNA and c-Jun protein. Inhibitors of RNA transcription and protein translation blocked both vinblastine-induced c-Jun expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…In this paper and our previous study, MEKK1-dependent JNK activation correlates strongly with apoptosis, and previous reports have shown that absence or inhibition of JNK resulted in decreased levels of apoptosis with vinblastine treatment [28], [29]. We also show that the JNK substrate c-Jun upregulation after vinblastine treatment is partially dependent upon MEKK1, and upregulation of c-Jun has been shown to contribute to vinblastine-induced apoptosis [30]. The duration of JNK activation may also be important for inducing apoptosis.…”
Section: Discussionsupporting
confidence: 83%
“…In this paper and our previous study, MEKK1-dependent JNK activation correlates strongly with apoptosis, and previous reports have shown that absence or inhibition of JNK resulted in decreased levels of apoptosis with vinblastine treatment [28], [29]. We also show that the JNK substrate c-Jun upregulation after vinblastine treatment is partially dependent upon MEKK1, and upregulation of c-Jun has been shown to contribute to vinblastine-induced apoptosis [30]. The duration of JNK activation may also be important for inducing apoptosis.…”
Section: Discussionsupporting
confidence: 83%
“…For these studies we used mainly KB-3 cells, a HeLa subline, because they undergo a welldefined and predictable time course of mitotic arrest followed by apoptosis when treated with antimitotic drugs. We have previously shown, and confirmed in this study, that vinblastine activates the classical JNK ⁄ AP-1 pathway [6,7] and promotes high levels of c-Jun expression, which occurs through a JNK-mediated auto-regulatory pathway [15]. Despite these advances, it is still not clear how the JNK ⁄ c-Jun pathway is activated in response to mitotic arrest caused by microtubule inhibitors.…”
Section: Discussionmentioning
confidence: 59%
“…Mitoxantrone induces p21 Cip1 [63]. Vinblastine induces apoptosis via reduction of p21 Cip1 [64]. Paclitaxol induces an Akt-dependent phosphorylation on p21 Cip1 leading to an association of p21 Cip1 with 14-3-3 and thus accumulation of the phosphorylated form of p21 Cip1 in cytoplasm which prevents the inhibitory effect of p21 Cip1 [65].…”
Section: Discussionmentioning
confidence: 99%